'Football Remembers' — the Collective Memory of Football in the Spectacle of British Military Commemoration. (2nd January 2023) - Fitzpatrick, Daniel
Abstract : This article examines two major rituals of contemporary national life in the UK: association football and military commemoration. It explores the ways in which remembering is enacted and performed within UK football and how these processes are related to issues of power, agency and identity in Britain today. Employing the concepts of collective memory and spectacle, this article argues that 'memory entrepreneurs' have sought to embed football as 'site of memory' in the performance of military commemoration. It concludes that this has contributed to the transformation of military commemoration, from a ritual that is observed to a spectacle that is consumed. This paper thus contributes to emergent debates on the militarization of civilian space, the shifting nature of civil–military relations in the twenty-first century, and the role of military remembrance in the reproduction of Britishness.